Regional gastric emptying and gastric contractile activity in functional dyspepsia: new approach optimizing the consensus protocol (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Consensus protocol organizes gastric emptying scintigraphy (GES). There is low adherence to the protocol, and its applicability is reduced due to poor connection between retention and functional disorders. To optimize the consensus protocol, we added a dynamic acquisition and quantification of distinct parameters for healthy and dyspeptic subjects. Fourteen patients with functional dyspepsia (FD) and 20 healthy volunteers were undergone GES. The dynamic acquisition was added to the activity versus time curve composed of 4-time points (0, 60, 120, and 240 min) preconized. A dynamic set of 3060 images (1 Hz) were acquired between immediate and 60 min static images. Regions of interest were drawn to divide the stomach internally, and two gastric segmentations (similar areas and incisura) were adopted for all quantification of global GE and contractile parameters. Gastric retention at 4-time points preconized was not enough to identify differences between FD and healthy volunteers (R² = 0.99; p ˂ 0.0009). Retention percentage of test meal in the proximal stomach employing segmentation, T1/2, MGET and lag phase analysis were higher in dyspeptic compared to healthy volunteers.  Impaired intragastric meal distribution was observed in FD by similar areas (p < 0.02) and incisura (p < 0.001). Reduction in the amplitude of contraction from the proximal region (p ˂ 0.015 and p ˂ 0.003) was observed in FD segmentation by similar areas and incisura, respectively. Impaired proximal stomach was observed in functional dyspepsia due to the insertion of dynamic acquisition proposed by consensus. Our approach can strengthen the consensus protocol and makes it capable of recognize and classify some diseases.